Projeto de qualificação docente (PQD - 1997/2001): um estudo sobre sua influência na formação e atuação dos licenciados em letras no pólo de Estância/SE - Siqueira, Maryluze Souza Santos (2006)
The present study aimed at investigating the influence of the Professors Qualification Project (PQD1) in the formation and performance of professors that belonged to the Literacy University Course. This project was implanted by the Federal University of Sergipe (UFS) in partnership with the Sergipe s Education Secretary (SEED) and the Foundation of Support to the Research in Sergipe (FAPESE). The PQD had as objective to foster the current professors which work in the public state schools and in the municipal education around Sergipe, as well. This data was collected in the POP s Coordination in Estância, using the conclusions of the Literacy Course s egresses, acquired in their own pedagogical practice throughout these years. Initially, it was presented a theoretical reflection on the State s responsibility while promoting the public politics, especially when refers to education. We also brought up a description of the Teaching Qualification s Project, specifying the reached objectives, goals, functioning and results. Describing and analyzing the data, we detached the PQD s influence in the Literacy Course egresses formation and development in regards to their personal and professional accomplishments, as well as their representation related to the PQD and the process of teaching.